2009
DOI: 10.1002/med.20150
|View full text |Cite
|
Sign up to set email alerts
|

The ozone paradox: Ozone is a strong oxidant as well as a medical drug

Abstract: After five decades characterized by empiricism and several pitfalls, some of the basic mechanisms of action of ozone in pulmonary toxicology and in medicine have been clarified. The present knowledge allows to understand the prolonged inhalation of ozone can be very deleterious first for the lungs and successively for the whole organism. On the other hand, a small ozone dose well calibrated against the potent antioxidant capacity of blood can trigger several useful biochemical mechanisms and reactivate the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
336
0
37

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(380 citation statements)
references
References 204 publications
7
336
0
37
Order By: Relevance
“…The unstable condition of medical ozone, which starts decaying (2 μg/mL) after about 20 s, allows a limited time for injection of no more than 15 s. Typically, no premedication is given, aseptic techniques are used, and the procedure is performed at an outpatient facility [1,2,25]. While ozone exposure has been linked to a number of adverse health effects [3], complications secondary to oxygen-ozone treatment are rare [5]. Nevertheless, its novel application as a percutaneous technique in treating spine disorders, especially at the lumbar spine, raises concerns about safety [30].…”
Section: Discussionmentioning
confidence: 99%
“…The unstable condition of medical ozone, which starts decaying (2 μg/mL) after about 20 s, allows a limited time for injection of no more than 15 s. Typically, no premedication is given, aseptic techniques are used, and the procedure is performed at an outpatient facility [1,2,25]. While ozone exposure has been linked to a number of adverse health effects [3], complications secondary to oxygen-ozone treatment are rare [5]. Nevertheless, its novel application as a percutaneous technique in treating spine disorders, especially at the lumbar spine, raises concerns about safety [30].…”
Section: Discussionmentioning
confidence: 99%
“…Prabakaran et al (2012) also reported that E.coli was highly sensitive to ozone treatment. According to Bocci et al (2009), the antimicrobial action of ozone results from the inhibition of the metabolic activity of microorganisms. Ozone is therefore capable of broad spectrum disinfection by destroying the viral DNA and acting in the formation of free radicals (Stübinger et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ozone AHT is also shown to improve the hemorrheologic properties and increase the oxygen delivery to the more ischemic tissues 317. The therapeutic oxidative stress caused by the AHT also leads to upregulation of the intracellular antioxidant enzymes and production of heme oxygenase-1 and heat-stable protein-70, which help in protecting the tissues from ischemia/reperfusion and inflammation and also play a role in wound healing 3111820. In our case, the patient was 59 years old and immunosenescence may also be a cause of impaired wound healing 21.…”
Section: Discussionmentioning
confidence: 99%